Bogactwo. Przyczynek do katolickiego ujęcia tej kategorii - Siek, Paweł (Annales. Etyka w Życiu Gospodarczym, 2015)
The article presents issues concerning the interpretation of the phenomenon of wealth in the context of Christian thought. From beginning, philosophical thought has been engaged in problems of tangible property and its influence on the human condition. The great philosophers indicated a way that the person should refer to the goods of this world. Plato, Aristotle, Seneca – each of them, according to his own vision of man and the world, referred in his texts to the problem of wealth. Equally significant contributions has been made by the monotheistic religions, Judaism and Christianity. Along with the development of the Church, this phenomenon stood out as an essential point of teaching. Primitive and post-apostolic church, to some extent out of necessity, took polemics with the outside world. Separating faith from matters of management, with its beginning in the Enlightenment, shaken the moral underpinnings of the deeds related to wealth. Marxist philosophy gave impulse to another reflection of the Church over economic phenomena. Leon XIII and his Rerum novarum are a milestone in Catholic thought on negative phenomena within the economy. The Holy Father portrayed threats resulting from the Marxist concept, showing an anthropological concept which was appropriate from the point of view of the Christianity. Social and later encyclicals, treat issues related to wealth from the Christian anthropology standpoint.